The Genetic Resources Policy Initiative newsletter: April 2006 - International Plant Genetic Resources Institute (2006)
GRPI has continued advancing the implementation of the '3M approach', i.e. the design of model processes for multi-stakeholder, multi-disciplinary and multi-sectoral cooperation to develop law and policy products as they relate to genetic resources for food and agriculture (GRFA). Phase 1 has been completed in all GRPI countries and implementation of Phase 2, mainly in the form of preliminary orientation and publicity workshops, has begun in several countries. The completion of Phase 1 activities has been a somewhat lengthier process than projected. However, this has allowed for a deeper discussion regarding the nature and objectives of proposed activities than might otherwise have been possible. In general, finalising of Phase 2 proposals has constituted a capacity building activity in itself through the process of analysing Phase 1 identified priorities and linking these with clear policy objectives. It is expected that Phase 2 will feature more active participation from all stakeholders. The task forces will continue to ensure broad-based participation, provide technical backstopping, and play an overall harmonizing role vis-à-vis the research, capacity building and awareness creating activities. The final products of GRPI Phase 2 will vary, depending on the priorities identified and the methodologies pursued. They will include: Strengthened capacity of domestic governments to 'mainstream' interdepartmental coordination and multistakeholder consultation concerning GRFA-related policy-making and implementation; Reports of national and sub-regional surveys; Research papers linking national sectoral activities, socio-economic analysis and development goals to policy options; Training materials and 'tools' to help national policy-makers 'think through' their options; Draft national policies and laws. The current status of Phase 2 implementation in the various country projects is described in this newsletter. This newsletter is an attempt to inform all our national partners and stakeholders of activities and events that are taking place in the Project. The unique design of this newsletter allows for quick and easy access to articles of interest to you. Simply review the headlines and the brief descriptions of the articles then click on the articles you wish to read in depth. New articles will be added every time we produce the newsletter. Older newsletters will be archived and may be made available upon request. There will be four editions of this newsletter. The purpose for having quarterly editions is to target information that is relevant to your needs. Finally we would like to extend our gratitude to all national partners and stakeholders who have played an instrumental role in our efforts aimed at strengthening capacity to analyse national options.